Minoans, Philistines, and Greeks, B.C. 1400-900 - Burn, A. R. (Andrew Robert), 1902-1991. Link ([S.l.])
1 online resource
Keywords: Minoans, Philistines, and Greeks (1930) presents a historical narrative of the fortunes of the Aegean people, including invaders of and fugitives from the Aegean area, from the end of the fifteenth to the end of the tenth century B.C. It traces the gradual decline and fall of the Aegean culture, the first advanced civilisation in Europe, and the migrations of peoples such as the Philistines and Phoenicians across the Mediterranean.